Ground state phase diagrams and ferroelectric hysteresis loops behaviour of dendrimer superlattice: a Monte Carlo study. Issue 22 (16th November 2020) - Sahdane, T.; Masrour, R.; Jabar, A.
ABSTRACT: In this current paper, we purpose a ferrielectric mixed (7/2;2) spins Ising model to describe the dendrimer superlattice using Monte Carlo study (MCs). The ground state phase diagrams of dendrimer superlattice with half and integer mixed spins in ( DS, EZ ), ( JσS, EZ ) and ( JσS, DS ) planes ( DS (or σ ): crystal field and Ez : Electric field) were obtained. Typical temperature dependences of thermodynamics quantities such as polarisation of the ferroelectric, internal energy and ferroelectric hysteresis loop were presented under the influence of various physical parameters (crystal filed, exchanges interactions, etc.). The ferroelectric phase diagram of critical temperature was obtained for several exchange interactions. We found some interesting ferroelectric hysteresis loops behaviour for certain physical parameters such as temperature, exchange interactions between spins mixed and crystal field applied on two spins. Our results are consistent with those obtained by some theoretical and experimental researches.